European cardiovascular nurses' and allied professionals' knowledge and practical skills regarding cardiopulmonary resuscitation. (1st April 2018) - Pettersen, Trond R; Mårtensson, Jan; Axelsson, Åsa; Jørgensen, Marianne; Strömberg, Anna; Thompson, David R; Norekvål, Tone M
Abstract: Purpose: Cardiopulmonary resuscitation (CPR) remains a cornerstone in the treatment of cardiac arrest, and is directly linked to survival rates. Nurses are often first responders and need to be skilled in the performance of cardiopulmonary resuscitation. As cardiopulmonary resuscitation skills deteriorate rapidly, the purpose of this study was to investigate whether there was an association between participants' cardiopulmonary resuscitation training and their practical cardiopulmonary resuscitation test results. Methods: This comparative study was conducted at the 2014 EuroHeartCare meeting in Stavanger ( n =133) and the 2008 Spring Meeting on Cardiovascular Nursing in Malmö ( n =85). Participants performed cardiopulmonary resuscitation for three consecutive minutes CPR training manikins from Laerdal Medical®. Data were collected with a questionnaire on demographics and participants' level of cardiopulmonary resuscitation training. Results: Most participants were female (78%) nurses (91%) from Nordic countries (77%), whose main role was in nursing practice (63%), and 71% had more than 11 years' experience ( n =218). Participants who conducted cardiopulmonary resuscitation training once a year or more ( n =154) performed better regarding ventilation volume than those who trained less (859 ml vs. 1111 ml, p =0.002). Those who had cardiopulmonary resuscitation training offered at their workplace ( n =161) also performed better regarding ventilation volume (889 ml vs. 1081 ml, p =0.003) and compression rate per minute (100 vs. 91, p =0.04) than those who had not. Conclusion: Our study indicates a positive association between participants' performance on the practical cardiopulmonary resuscitation test and the frequency of cardiopulmonary resuscitation training and whether cardiopulmonary resuscitation training was offered in the workplace. Large ventilation volumes were the most common error at both measuring points.